1976
DOI: 10.1007/bf00594602
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic pressures within the vascular structures of the rat kidney

Abstract: The pressure conditions at the distal end of the interlobular arteries and in the interlobular veins were investigated from the pressures obtained in superficial small arteries and veins, accidentally found on the kidney surface, during the subsequent blockade of the blood stream in the down-stream and up-stream direction, respectively. The results suggested a hydrostatic pressure in the distal end of the interlobular arteries of about 85 mm Hg under normotensive conditions-a pressure which remained fairly con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(39 citation statements)
references
References 18 publications
2
37
0
Order By: Relevance
“…The main conclusion of the present study is similar to that of Kallskog et al [2]: un der normotension, the preglomerular resis tance is shared about evenly by the ILA and the afferent arteriole. (To avoid repeating the errors of the past, one should probably rather refer to the sum of series resistance of the renal artery, the interlobar, arcuate and interlobular arteries, instead of a priori assuming that the ILA is responsible for the whole resistance between aorta and the af ferent arteriole.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The main conclusion of the present study is similar to that of Kallskog et al [2]: un der normotension, the preglomerular resis tance is shared about evenly by the ILA and the afferent arteriole. (To avoid repeating the errors of the past, one should probably rather refer to the sum of series resistance of the renal artery, the interlobar, arcuate and interlobular arteries, instead of a priori assuming that the ILA is responsible for the whole resistance between aorta and the af ferent arteriole.…”
Section: Discussionsupporting
confidence: 79%
“…They con cluded that a considerable fraction of the glomerular resistance may reside in the ILA. Support of this view came from Kallskog et al [2]: they detected in some rats a modified ILA, giving off efferent arterioles, but ex tending all the way out to the renal capsule. End pressure in these arteries, measured af ter occlusion of the capsular branches, was 30-40 mm Hg lower than aortic pressures of about 120 mm Hg.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Combining the data on glomerular pressure and the glomerular blood flow measured by the microsphere technique and measurements of the hydrostatic pressure in the subcapsular part of the interlobular artery in the Sprague-Dawly rat kidney, Kjallskog et al 19 calculated the variation of vascular flow resistance in the interlobular artery and in the afferent and efferent arterioles during autoregulation. They concluded that the variation of the renal vascular resistance during autoregulation in the rat was restricted mainly to the interlobular artery and that the outer cortex exhibited almost no autoregulation.…”
Section: Figure 3 Relationship Between Microsphere Diameter and Ratiomentioning
confidence: 99%
“…Each type of kidney responded within seconds to the pressure change to adjust blood flow toward the control values. This type of response has been suggested to indicate a myogenic re sponse by the vasculature [11,[13][14][15], Stron ger evidence for a myogenic or nontubular component to the autoregulatory response is provided by the fact that, in the present study, the kidneys without glomerular filtra tion still adjusted renal vascular resistance appropriately to changes in perfusion pres sure. Thus, part of the autoregulatory re sponse is mediated through a nontubular mechanism, most likely a myogenic mecha nism.…”
Section: Discussionmentioning
confidence: 52%